Concrete for underground structures guidelines for design and construction - Goodfellow, Robert J. F. (Society for Mining, Metallurgy, and Exploration, 2011)
Concrete is a vital component of almost every underground construction project. Because it significantly impacts both the durability and cost of a project, owners, designers, and contractors are constantly challenged with designing and placing the concrete to meet their quality standards in the most cost-effective way. Concrete for Underground Structures: Guidelines for Design and Construction can make that task a lot easier. Instead of searching pages of scattered reference materials when writing specifications, this book is a one-source guide to help you quickly find the answers you need.